(untitled) (Revista Contexto & Saúde, 2026)
Eugenia klotzschiana O. Berg is an endangered species endemic to the Cerrado whose therapeutic potential has yet to be fully elucidated. Few studies have shown this plant has antimicrobial, antiparasitic, and antioxidant activity. In this study, the activity of the ethanolic extract of the leaves of E. klotzschiana O. Berg against Gram-positive bacteria was evaluated by determining the antimicrobial and antibiofilm activity. All the bacteria were able to form biofilm, with Staphylococcus aureus ATCC 6538 and Staphylococcus aureus ATCC 29213 being classified as strong biofilm formers, Enterococcus faecalis ATCC 51299, Staphylococcus epidermidis ATCC 12228, Enterococcus faecalis ATCC 19433 and Staphylococcus epidermidis ATCC 14990 as moderate biofilm formers. The ethanolic extract showed slight antimicrobial activity, but was active against biofilm formation at concentrations ranging from 0.039 to 1.250 mg.mL-1. We conclude that the ethanolic extract was active against the biofilm formation of Gram-positive bacteria, and that further studies with E. klotzschiana O. Berg should be carried out to confirm the plant’s therapeutic potential.